PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, KOMUNIKASI DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU SMA NEGERI SE-KECAMATAN PEUSANGAN KABUPATEN BIREUEN - Nita Zahara; Raihan Iskandar (LPPM-UNIKI, 2023)
This study aims to determine the effect of Principal Leadership, Communication and Organizational Culture on Teacher Performance, both partially and simultaneously. The object of research were 139 public high school teachers in Peusangan District, Bireuen Regency. In the form of quantitative research with associative type, and problem analysis through path analysis approach. The results of the study show that there is an influence of (1) the leadership of the principal on teacher performance by 31.16%. (2). The communication factor on teacher performance is 43.22%. (3). Organizational culture on teacher performance is 35.94%. (4). Simultaneously the principal's leadership, communication and organizational culture have a significant effect and contribute to teacher performance by 40.3%.